Dual time point imaging fluorine-18 flourodeoxyglucose positron emission tomography for evaluation of large loco-regional recurrences of breast cancer treated with electrochemotherapy - Matthiessen, Louise Wichmann (Versita, Warsaw, 2013)
BACKGROUND: Electrochemotherapy is a local anticancer treatment very efficient for treatment of small cutaneous metastases. The method is now being investigated for large cutaneous recurrences of breast cancer that are often confluent masses of malignant tumour with various degrees of inflammation. To this end 18-Flourine-Flourodeoxyglucose-Positron Emission Tomography/Computed Tomography (FDG-PET/CT) could be a method for response evaluation. However, a standard FDG-PET/CT scan cannot differentiate inflammatory tissue from malignant tissue. Dual point time imaging (DTPI) FDG-PET has the potential of doing so. The purpose of this study was to investigate if DTPI FDG-PET/CT could assess response to electrochemotherapy and to assess the optimal timing of imaging. PATIENTS AND METHODS: Within a phase II clinical trial 11 patients with cutaneous recurrences had FDG-PET/CT scans at three time points: 60 min, 120 min and 180 min after FDG injection. The scans were performed before and 3 weeks after electrochemotherapy. RESULTS: A significant reduction in maximum standard uptake value at 60 min post injection was seen after treatment. Furthermore a change in the FDG uptake pattern was observed; from increasing uptake in up to 180 min post injection before treatment to stabilization of FDG uptake at 120 min post injection after treatment. The change in FDG uptake pattern over time lead to change of response in three target lesions; two lesions changed from stable metabolic disease to partial metabolic response and one lesion changed from partial metabolic response to stable metabolic disease. To ensure detection of the change in uptake pattern, scanning 60 and 180 min post injection seems optimal. CONCLUSIONS: The present study shows that FDG-PET/CT 60 and 180 min after tracer injection is a promising tool for response evaluation of cutaneous recurrences of breast cancer treated with electrochemotherapy.